Improving Students’ Speaking Performance By Using Autoplay Media At SMAS Darul Hikmah Mataram - Salim, Agus; Firman, Edi; Rosida, usratun (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
This research was aimed to describe using Autoplay Media to Improve Students’ Speaking Performance at SMAS Darul Hikmah Mataram. The model of this research was classroom action research. This research focused on improving of the students’ speaking performance by using Autoplay Media. This research consisted of one cycle include the classroom action research model such as: planning, acting, observing, and reflecting. In this research, the researcher toke the XI IPS of SMAS Darul Hikmah Mataram. The instrument that used by the researcher in this study were test, recording, and observation sheet to measure the students result. Based on the result of data analysis the mean score of students’ achievement in the first cycle was 45.05 in the pre-test and the percentage was 21.05% and post-test was 79.36, percentage was 78.94%. So the researcher concluded that the score of the students’ speaking performance was higher than minimum Complete Criteria Success (KKM), in which the KKM of SMAS Darul Hikmah Mataram was 75. So, it could be concluded that this research was successful and could increase students’ speaking performance.